Effects of titanium dispersion state on distribution and reactivity of active centers in propylene polymerization with MgCl2‐supported Ziegler‐Natta catalysts: A kinetic study based on active center counting. Issue 20 (11th September 2020) - Jiang, Baiyu; Zhang, Biao; Guo, Yintian; Ali, Amjad; Guo, Wenqi; Fu, Zhisheng; Fan, Zhiqiang
Abstract: Kinetics of propylene polymerization with two TiCl4 /MgCl2 model catalysts of different Ti load (Cat‐1: Ti 0.1 wt%; Cat‐2: Ti 1.0 wt%) was investigated in this work. Time‐dependent variations of active centers fraction ([C * ]/[Ti]) and active center distribution of the two catalysts were compared. In propylene polymerization with Cat‐1, [C * ]/[Ti] was only 7.8 % in the initial stage, but increased for more than three times in reaction period of 600 s. Propylene polymerization with Cat‐2 had much lower [C * ]/[Ti]. Active center distributions of the two catalysts were markedly different. Cat‐1 has evidently higher proportion of aspecific active centers and less isospecific ones than that of Cat‐2. These catalysts also showed different time‐dependent variations of active center distribution. The chain propagation rate constant of isospecific centers in Cat‐2 was evidently higher than that in Cat‐1, but propagation rate constants of either aspecific and medium‐isospecific centers were only slightly changed by enhancing Ti content of the catalyst. The results suggest that isospecific centers are mainly originated from clustered Ti species, but non‐clustered Ti species are the main source of active centers with lower stereoselectivity. By considering factors like dispersion states of Ti species and release of shielded active species through disintegration of catalyst particles, active center models have been proposed to explain the different kinetic behaviors of the two model catalysts. Abstract : Propylene polymerization with two TiCl4 /MgCl2 model catalysts (Cat‐1: Ti 0.1 wt%; Cat‐2: Ti 1.0 wt%) was compared. Cat‐1 has higher proportion of aspecific active centers and less isospecific ones than Cat‐2. They also showed different time‐dependent variations of active center distribution. Chain propagation rate constant ( k p ) of isospecific centers in Cat‐2 was evidently higher than that in Cat‐1, but k p values of aspecific and medium‐isospecific centers were only slightly changed by enhancing Ti content of the catalyst.